Alexithymia and Autistic Traits: Associations With Social and Emotional Challenges Among College Students - Vaiouli, Potheini; Panayiotou, Georgia (Frontiers in Neuroscience, 2021)
Background: Alexithymia is a multifaceted personality construct defined by marked difficulties in identifying and describing feelings and in externally oriented thinking. Given its intrinsic role in social-emotional processing, alexithymia is now recognized as a trans-diagnostic trait in a range of neurodevelopmental disorders, including autism. Research has pinpointed to the co-occurrence of autism with characteristics typical of alexithymic normative samples, such as social-communication difficulties and decreased emotion regulation abilities. Nonetheless, the role of individual facets of alexithymia in predicting challenges in social communication functioning is still understudied. Methods: In total, 275 young adults completed the Toronto Alexithymia Scale, the Autism Spectrum Quotient (short form), the Interpersonal Competence Questionnaire, and the Difficulties in Emotion Regulation Scale self-reported questionnaires for assessing alexithymic and autistic traits, social-communication abilities, and emotion regulation difficulties. We used regression models to establish cross-sectional associations between autism, alexithymia, and social-emotional difficulties. Also, we ran a parallel mediation analysis to determine whether the relationship between autistic traits and emotion regulations challenges are mediated by Alexithymia facets. Results: Analysis showed a significant positive association between autistic traits and alexithymic traits and between autistic traits and emotion regulation difficulties while, as expected, autistic traits were negatively correlated with social skills. A significant relationship was found among the participants’ levels of alexithymia and their interpersonal skills with two of three alexithymic subscales significantly contributing to the model. Similarly, a significant relationship was found among alexithymia subscales and emotion regulation difficulties with all three alexithymia subscales being statistically significant. Finally, analysis on two mediator models indicated a significant effect of autistic traits on social skills mediated by alexithymic traits as well as a significant indirect effect of autistic traits on emotion regulation difficulties mediated by alexithymic traits. Conclusion: The results of this study provide evidence of the influence of different alexithymic facets on the relationship between autistic traits and social-emotional challenges in young adults. Longitudinal studies may explore further alexithymia and its associations with social-emotional difficulties in autism as well as the potential implications of these findings in intervention and treatment programs.